Comparison the Effect of Bromelain Enzyme, Phosphoric Acid, and Polyacrylic Acid Treatment on Microleakage of Composite and Glass Ionomer Restorations - Farahnaz Sharafeddin; Paniz Moraveji (Journal of Dentistry, 2022)
Statement of the Problem: Resin modified glass-ionomer cement (RMGIC) shows low microleakage values. Bromelain enzyme is a deproteinizing agent with an anti-inflammatory effect in human body.Efective cavity treatment is an important factor in reduction of microleakage. Purpose: The aim of this study was to determine the effectiveness of the deproteinizing aspect of 10% bromelain enzyme on the microleakage of RMGIC and composite restorations. Materials and Method: In this experimental study, 40 non-carious extracted human molar teeth were categorized in eight experimental groups (n=5). Standard class V cavities were prepared on the buccal and lingual surfaces of the teeth (n=10). The specimen were classified as Group 1, in which 20% polyacrylic acid (PAA) was applied on the teeth then treated with 10% bromelain enzyme; Group 2: 10% bromelain enzyme was applied; Group 3: 10% bromelain enzyme was applied and then treated with polyacrylic acid; Group 4: 20% polyacrylic acid was applied. Groups1 to 4 were restored with RMGIC (Fuji II LC, GC, Japan). Group 5: etched by 37% phosphoric acid and then treated by 10% bromelain; Group 6: 10% bromelain enzyme was applied without etching; Group 7: teeth were deproteinized with 10% bromelain enzyme and then etched with 37% phosphoric acid; and Group 8: cavities were etched with 37% phosphoric acid. In the groups 5 to 8, Adper single bond (3M, ESPE, USA) and filled with composite resin Z350 (3M, ESPE, USA). After thermocycling, the teeth were sectioned. Microleakage scores were measured using stereomicroscope (40×). Kruskal-Wallis and Mann-Whitney tests were used for data analysis (p< 0.05). Results: Statistical analysis did not show any significant difference in occlusal and gingival margin microleakage in glass ionomer groups (1-4) (occlusal p= 0.218, gingival p= 0.192). Kruskal-Wallis revealed significant difference in occlusal and gingival margin microleakage of Groups 5 to 8 (occlusal p= 0.006 and gingival p= 0.00). Group 5 demonstrated the lowest occlusal microleakage (occlusal mean=0.00). Conclusion: Applying bromelain or polyacrylic acid did not affect the microleakage of glass ionomer filling. Due to the antinflamatory effects of bromelain, we suggest using it instead of PAA. Pretreatment of 10% bromelain enzyme after phosphoric acid significantly decreased microleakage in the occlusal and gingival margin of composite filling.